Peranan Edukasi Bidan dalam Mencegah Kurang Energi Kronis (KEK) pada Ibu Hamil di Provinsi Sulawesi Tengah - Tempali, Sri Restu; Sumiaty, Sumiaty (Poltekkes Kemenkes Palu, 2019)
Basic Health Research in 2013 recorded the prevalence of Chronic Energy Deficiency (SEZ) in pregnant women nationally reaching 24.2 percent, an increase from 2010 (18.8 %%) and 2007 (10.9%). The prevalence of SEZs in Central Sulawesi Province in 2013 was 32.6%, higher than the national average. Nutritional status monitoring in Central Sulawesi Province reported a prevalence of KEK Risk in pregnant women in 2015 of 32.6%. Districts with the highest prevalence were consecutively in Banggai Kepulauan District (67.8%), Tojo Una-Una District (51.9%), Sigi District (46.4%), Donggala District (36.7%), and Palu City (35.4%). Midwives in providing services to the community, especially pregnant women, always strive to prepare pregnant women since the first contact during prenatal care provides counseling or education to every pregnant mother about nutritional needs during pregnancy. This study aims to determine the role of midwives education in preventing SEZ in pregnant women in Central Sulawesi Province. Observational research with a study design crossectional. Sampling using the proportional random sampling technique with a total sample of 98 midwives in the working area of 4 selected districts, namely Banggai Islands District (15 samples), Sigi District (18 samples), Donggala District (25 samples) and Palu City (40 samples). The results of the study showed that the midwives who carried out the role of education to pregnant women in their regions mostly did not have the incidence of pregnant women with SEZ (83.1%). The results of the analysis Chi-Square obtained a p-Value value of 0.041, which means that there is a relationship between the role of midwife education and prevention of SEZ events in pregnant.